INTEGRATION OF RENEWABLE ENERGY SOURCES IN SMART GRID: A REVIEW - Zafar, S.; Nawaz, K.; R. Naqvi, S. A.; Malik, T. N. (The Nucleus, 2013)
The increasing complexity of the existing power grid due to rapid population growth, development in technology, infrastructure and computational tools are the factors that contribute to the need of deployment of smart grid for secure and efficient use of electrical energy.The modernization of electric grids toward a smart grid is being carried out to improve reliability, facilitate integration of renewable energies, and improve power consumption management.Due to continuous depletion of primary fuel resources and global concern about the environmental pollution, the development of smart grids based on renewable energy resources has gained huge strategic significance now a days to resolve the energy crisis. However the intermittent and fluctuating nature of these sources makes the integration a difficult task that needs to be effectively addressed. Firstly this paper briefly discuss the emerging renewable energy resources (RERs) and Energy storage systems (EES).Secondly this work comprehensively reviews the potential challenges in integration of these sources in smart grid along with the applied control strategies for their facilitation and some practical case studies.